2003
DOI: 10.1073/pnas.0333065100
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-limited kinetics of the solution–solid phase transition of molecular substances

Abstract: For critical tests of whether diffusion-limited kinetics is an option for the solution-solid phase transition of molecular substances or whether they are determined exclusively by a transition state, we performed crystallization experiments with ferritin and apoferritin, a unique pair of proteins with identical shells but different molecular masses. We find that the kinetic coefficient for crystallization is identical (accuracy <7%) for the pair, indicating diffusion-limited kinetics of crystallization. Data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
131
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(142 citation statements)
references
References 36 publications
(65 reference statements)
8
131
1
Order By: Relevance
“…. '' (29). The same diffusion-limited kinetics and potential energy barriers were also shown to control incorporation of small inorganic molecules into solids such as CaCO 3 crystals (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…. '' (29). The same diffusion-limited kinetics and potential energy barriers were also shown to control incorporation of small inorganic molecules into solids such as CaCO 3 crystals (29).…”
Section: Discussionmentioning
confidence: 99%
“…4 shows that increasing positive values of molecular hydrophilicity correlate well with step propagation rates. A possible explanation for this effect comes from recent experimental studies of step dynamics during growth from solutions (29). There it was concluded that the rate-limiting step during crystallization was desolvation of the solute, where the barrier to desolvation was that associated with bulk diffusion limited by the restructuring of water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CNT describes the formation of nuclei from the dynamic and stochastic association of monomeric units (e.g., ions, atoms, or molecules) that overcome a free-energy barrier at a critical nucleus size and grow out to a mature bulk phase. Calcium carbonate (CaCO 3 ) is a frequently used model system to study nucleation (3)(4)(5); however, despite the many years of effort, there are still phenomena associated with CaCO 3 crystal formation where the applicability of classical nucleation concepts have been questioned (6). These include certain microstructures and habits of biominerals formed by organisms (7), or geological mineral deposits with unusual mineralogical and textural patterns (8).…”
mentioning
confidence: 99%
“…We propose that a dense liquid phase (containing 4-7 H 2 O per CaCO 3 unit) forms in supersaturated solutions through the association of ions and ion pairs without significant participation of larger ion clusters. This liquid acts as the precursor for the formation of solid CaCO 3 in the form of vaterite, which grows via a net transfer of ions from solution according to z Ca 2+ + z CO 3 2− → z CaCO 3 . The results show that all steps in this process can be explained according to classical concepts of crystal nucleation and growth, and that long-standing physical concepts of nucleation can describe multistep, multiphase growth mechanisms.…”
mentioning
confidence: 99%